EFFECTS OF PHYSICAL ACTIVITY ON CHILDREN’S DEVELOPMENT – A REVIEW - Marzena Walasek; Michał Ziemba; Katarzyna Giedzicz; Rafał Kulgawczuk; Jan Smusz (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Physical activity is vital for the holistic development of children, benefiting physical, cognitive, social, and emotional domains. Engaging in regular physical activities from an early age fosters a healthy body, emotional and social well-being, and cognitive development.Aim: This study explores the diverse benefits of physical activity on childhood development, focusing on physical health, cognitive functions, social skills, and emotional well-being.Materials and Methods: A comprehensive literature review was conducted, analyzing existing research on the impact of physical activity on various aspects of childhood development. Searches were performed across databases such as PubMed and Google Scholar using keywords like "childhood physical activity" and "childhood sport."Results: Physical activity promotes healthy growth, enhances cardiovascular and musculoskeletal health, and helps maintain a healthy weight, reducing obesity risks. It improves memory, attention, and executive functions, contributing to better academic performance. Socially, it fosters peer relationships, enhances social skills, and cultivates leadership qualities. Emotionally, it aids in emotional regulation, boosts self-esteem, and reduces anxiety and depression.Discussion: The findings highlight the multifaceted benefits of physical activity on children's development, corroborating existing literature. Despite robust evidence, limitations such as reliance on self-reported data and cross-sectional study designs constrain causal inferences. Future research should use objective measures and longitudinal approaches, considering interactions with diet, sleep, and lifestyle factors.Conclusion: Physical activity significantly benefits childhood development across physical, cognitive, social, and emotional domains. Addressing limitations in existing research will enhance the understanding and application of physical activity in promoting holistic child development.